The Effect of Symmetric and Asymmetric Loading of Frontal Segment with Two Curved Cantilevers: An In Vitro Study - Malgorzata Bilinska; Michel Dalstra (MDPI AG, 2022)
Cantilevers generate statically determined force systems. The frontal segment loading with symmetric and asymmetric cantilevers in a three-piece intrusion base arch can be used to correct midline asymmetry. Three types of 0.017" × 0.025" beta-titanium cantilevers: tip-back (TB), deep curve (DC), utility arch (UA) were tested on typodonts simulating intrusion of the maxillary anterior segment. Typodonts with symmetric and asymmetric cantilevers were scanned with intraoral scanner (3Shape, TRIOS, Copenhagen, Denmark) before (T0) and after (T1) the experiment, scans were superimposed using Mimics software (Materialise, Leuven, Belgium). Data were analysed with qualitative analysis. All cantilevers generated vertical and horizontal forces. For symmetric design, the DC and TB displayed intrusive force with retrusive component, UA intrusion and protrusion. The asymmetric cantilevers produced transverse displacement of anterior segment. DC created lateral, UA medial force, the anterior segment displacement was consistent with the used configuration. The movement of an anterior segment with TB is smaller compared to DC and UA. Symmetric cantilevers configurations can achieve simultaneous intrusion and retrusion or protrusion of the anterior segment. The asymmetric design with transversal force can clinically aid the correction of midline discrepancies. The effect of the cantilever configuration on delivered force direction was confirmed.